Doped bentonitic grouts for implementing performances of low-enthalpy geothermal systems - Marco Viccaro (Geothermal Energy, 2018)
Abstract Mechanical (flexural and uniaxial compressive strengths) and physical (thermal conductivity) properties of two new bentonitic grouts doped with 5 and 10% of graphite powder are discussed in this work and evaluated for their potential use in low-enthalpy geothermal applications. The same tests have been also conducted on a pure starting material (bentonitic grout) already present on the market and used to seal geothermal probes into boreholes. Experimental data show that the addition of 5 and 10% of graphite powder positively alters the mechanical properties of the doped bentonitic grouts, i.e., both flexural and uniaxial compressive strengths increased with respect to those of the pure material. Thermal conductivity also improved up to 60% in the doped bentonitic grouts. A simple analysis of the cost/benefit ratio suggests, however, that the bentonitic grouts doped with 5% of graphite powder is more suitable and competitive for a launch on the market and utilization as a sealing material in boreholes aimed at low-enthalpy geothermal installations. Implementation of thermal properties of the grout material implicates a reduction of the total borehole length of 15–20%.